2017
DOI: 10.5194/nhess-17-277-2017
|View full text |Cite
|
Sign up to set email alerts
|

The catastrophic landfill flowslide at Hongao dumpsite on 20 December 2015 in Shenzhen, China

Abstract: Abstract. A catastrophic flowslide occurred at the Hongao dumpsite on 20 December 2015 in the Guangming New District of Shenzhen, China. The flowslide caused 77 causalities and damaged 33 buildings. In the absence of extreme weather conditions and seismic activity, the causes of the failure were analyzed on the basis of multi-temporal remote-sensing images, site investigation, in situ tests, laboratory tests, and numerical analyses. Site investigations showed that the volume of the displaced material was 2.32 … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(9 citation statements)
references
References 27 publications
0
9
0
Order By: Relevance
“…A landslide occurred in the Guangming New District of Shenzhen (China) on December 20, 2015, which was caused by the instability of a large artifcial landfll [30]. Approximately 2.73 × 10 6 m 3 of construction spoil was mobilized with an impact area of 0.38 km 2 in this landslide (Figure 3 How the sliding body avalanches such a long distance on such relatively fat terrain and obtains such a high velocity is the main focus of the researchers [15,19,[30][31][32].…”
Section: The 2015 Shenzhen Landslide and Its Modelingmentioning
confidence: 99%
See 2 more Smart Citations
“…A landslide occurred in the Guangming New District of Shenzhen (China) on December 20, 2015, which was caused by the instability of a large artifcial landfll [30]. Approximately 2.73 × 10 6 m 3 of construction spoil was mobilized with an impact area of 0.38 km 2 in this landslide (Figure 3 How the sliding body avalanches such a long distance on such relatively fat terrain and obtains such a high velocity is the main focus of the researchers [15,19,[30][31][32].…”
Section: The 2015 Shenzhen Landslide and Its Modelingmentioning
confidence: 99%
“…Studies have shown that the high-velocity and longrunout distance characteristics of the Shenzhen 2015 landslide are mainly due to the high-water content and high initial pore pressure in the source area of the landslide [15,30,31,33]. Te low permeability of soil results in a signifcant increase in pore pressure during the sliding [15].…”
Section: The 2015 Shenzhen Landslide and Its Modelingmentioning
confidence: 99%
See 1 more Smart Citation
“…Meteorological conditions were scored medium-low risk, however the evidence is lacking to assess the prevalence of harm from these hazards. (Blight, 2008;Jayaweera et al, 2019;Lavigne et al, 2014;Nikulishyn et al, 2020;Xu et al, 2017;Yin et al, 2016).  These incidents impact local area swamping land, destroying houses and ruining communities.…”
Section: Risk Characterisation For Meteorological and Geophysical Hazmentioning
confidence: 99%
“…For example, a catastrophic landslide occurred at Hongao dumpsite on Dec 20, 2015, in Shenzhen, Guangdong, Southeast China. The landslide caused 69 causalities with 8 missings, damaged 33 buildings and caused near 800 million RMB economic loss (Xu et al, 2016), related soil and water conservation engineers were arrested. For the safe operation of the principal part of the project, the implementation of soil and water conservation projects is essential for constructive and productive engineering.…”
Section: Threatening Safetymentioning
confidence: 99%